O veneno do branco e a cura da terra: contribuições ao estudo da subjetividade a partir dos akroá-gamella do território aquaritiua (MA) - SANTOS NETO, Francisco Valberto dos (2022)
The indigenous people are an ethnic multiplicity of human groups that live, inhabit and reproduce their social relationships in a unique way, engendering their existence from references of different knowledge of the modern and Western epistemological organization. These existential territories related to terra imply conceptions of subjectivities that express the emergence of other worlds. In that sense, or present work has the objective of investigating the production process of the subjectivity of the Akroá-Gamella do Território Taquaritiua, located in the state of Maranhão, 231 kilometers from the capital São Luís. This investigative process analyzes two dimensions of the existence of Akroá-Gamella: the Retaken and the Enchanted. At first, it refers to a process of territorial and existential recovery that has been, for a long time, coexisting with violent interdictions. In the second dimension concerns the beings that inhabit the land, the forest and the waters and age together with the indigenous people both to protect the territory and to heal the land, in addition to conforming to the existence of the Akroá-Gamella. This work, from an ethnographic point of view, characterized by the insertion of the researcher in the territory and in the social relations of two subjects who work, part of the decolonial thought to analyze the social context in which we are inserted. This thought also enables a critical reflection on the modern humanist a priori that Psychology is inserted, or which makes it impossible to explore other worlds and other existences that are not organized from its image of thought. Likewise, this research aims to contribute to the construction of a Psychology that can act together with the indigenous people from their own perspectives. In the case of Akroá Gamella, understand their therapeutic and healing processes and be attentive to their existential dimensions that mobilize and transform traumatic events into positive creative forces.